Male chauvinism cyber-violence on Intagram: Analysis of 24 accounts - Bajo-Pérez, Irene (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This research aims to study how chauvinism violence is carried out on Instagram. The purpose of this study is to answer the following questions: Does the number of followers that women have on their Instagram account influence the male chauvinism they receive? Does the type of content that women frequently share on their Instagram condition the percentage of male chauvinism they receive? Does the types of male chauvinism received vary depending on the type of content that women frequently share on their Instagram account?